Effectiveness of acupressure therapy in cancer patients with constipation - Munqiidz Zahrawaani (Health Dynamics, 2024)
Research shows constipation is poorly treated in hospitalized children (3). This research is strengthened by the results of research which found that constipation had not received proper treatment in the treatment room for children with cancer (5). Pediatric patients who experience constipation can be influenced by several factors such as a low fiber diet, immobilization, and use of medications (3,5).: Background: acupressure is effective in reducing constipation in patients with advanced cancer (8). Therefore, this research was conducted to determine the effectiveness of acupressure in cancer patients experiencing constipation at the Indonesian National Hospital. Methods: experimental research methods on cancer children with the health problem of constipation. Results: Before receiving acupressure therapy, the average patient had not defecated for 81 hours. Changes occurred after therapy, namely patients experienced defecation an average of 9.2 hours. Conclusions: The changes show that acupressure therapy is very significant in reducing constipation.